Hadith as a Source of Islamic Law: Its Role and Significance - Ni'mah. SM, Khairatun; Arifi, Ahmad; Abror, Indal (Studi Multidisipliner: Jurnal Kajian Keislaman, 2024)
This study aims to examine hadith as a source of Islamic law, its role and significance. This study uses a library research type. The data analysis technique used in this study is the content analysis method, which is a technique used to identify each word, sentence in a text or series of texts, concepts, or themes. Researchers use data sources from books and analyze components related to the formulation of the problem. The results of this study explain that hadith is everything that comes from the Prophet Muhammad, both the words, actions, or approvals of the Prophet Muhammad, which are prescribed to humans. Hadith also has an important role as the second source of law and a guide to life for Muslims, after the Qur'an. Not only that, some important aspects of hadith in the lives of Muslims include providing explanations and details of the Qur'an, as a guide to morals and ethics, can strengthen a person's faith, and can build social harmony. Therefore, understanding hadith is very important for Muslims to build a life that is in harmony with Islamic teachings and create a harmonious and civilized society.